Seakeeping Performance and Passenger Comfort Assessment of a 300 GT Ro-Ro Ferry Using RAO, MSI, and MII Analyses - Wahidah, Jusma; Ariani, Vidya Rezeki; Alamsyah; Wulandari, Amalia Ika; Suwedy, Wardina; Sitorus, Chris Jeremy Verian; Hariyono; Kustiwansa, Harlian; Agusty, Cindy Lionita; Syam, Muhammad Anjas (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
This study examines the motion response and onboard comfort of a Ro-Ro ferry under varying wave directions and speeds using the Response Amplitude Operator (RAO), Motion Sickness Incidence (MSI), and motion-induced interruptions (MII) as evaluation parameters. Simulations were conducted using Maxsurf Motion software with wave heights of 3 m and 3.5 m and encounter angles of 0° (following seas), 90° (beam seas), and 180° (head seas) at vessel speeds of 0 and 12 knots. The MSI was assessed using both simulation results and empirical calculations, whereas the MII was evaluated according to the ISO 2631 standards at three onboard locations: the passenger, navigation, and vehicle decks. The RAO results indicate that the vessel met the NORDFORSK (1987) motion criteria under following and head seas but exceeded the roll limits in beam seas. The MSI values remained within the moderate comfort range, except under head seas at 12 kn, where the values approached the alert thresholds. The MII remained within acceptable levels under most conditions, although probable interruption levels were observed on the passenger and vehicle decks during beam sea conditions. Overall, the findings emphasize that wave direction and vessel speed significantly influence motion-induced discomfort and operational performance, underscoring the importance of optimizing route planning and speed to improve passenger safety and seakeeping performance on roll-on/roll-off ferries.